A r 1 0 43 e 23 d 2 2 3 cos b r 1 1 4 3 sin

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x) = x + x2 + x3 + x4 + · · · 1−x 2 6 12 17. ex = 1 + x + x2 /2 + x3 /3! + · · · + xk /k ! + · · · , e−x = 1 − x + x2 /2 − x3 /3! + · · · + (−1)k xk /k ! + · · · ; sinh x = 1x e − e−x = x + x3 /3! + x5 /5! + · · · + x2k+1 /(2k + 1)! + · · · , R = +∞ 2 cosh x = 1x e + e−x = 1 + x2 /2 + x4 /4! + · · · + x2k /(2k )! + · · · , R = +∞ 2 18. tanh x = 19. x + x3 /3! + x5 /5! + · · · 1 2 17 7 = x − x3 + x5 − x + ··· 1 + x2 /2 + x4 /4! + · · · 3 15 315 −1 3 4x − 2 = + = − 1 + x + x2 + x3 + x4 + · · · + 3 1 − x + x2 − x3 + x4 + · · · x2 − 1 1−x 1+x = 2 − 4x + 2x2 − 4x3 + 2x4 + · · · 20. 1 2 x3 + x2 + 2x − 2 =x+1− + x2 − 1 1−x 1+x = x + 1 − 1 + x + x2 + x3 + x4 + · · · + 2 1 − x + x2 − x3 + x4 + · · · = 2 − 2x + x2 − 3x3 + x4 − · · · 21. (a) (b) 22. (a) (b) 23. (a) d 1 − x2 /2! + x4 /4! − x6 /6! + · · · = −x + x3 /3! − x5 /5! + · · · = − sin x dx d x − x2 /2 + x3 /3 − · · · = 1 − x + x2 − · · · = 1/(1 + x) dx d x + x3 /3! + x5 /5! + · · · = 1 + x2 /2! + x4 /4! + · · · = cosh x dx 1 d x − x3 /3 + x5 /5 − x7 /7 + · · · = 1 − x2 + x4 − x6 + · · · = dx 1 + x2 1 + x + x2 /2! + · · · dx = (x + x2 /2! + x3 /3! + · · ·) + C1 = 1 + x + x2 /2! + x3 /3! + · · · + C1 − 1 = ex + C (b) x + x3 /3! + x5 /5! + · · · = x2 /2! + x4 /4! + · · · + C1 = 1 + x2 /2! + x4 /4! + · · · + C1 − 1 = cosh x + C Exercise Set 11.10 400 x − x3 /3! + x5 /5! − · · · dx = x2 /2! − x4 /4! + x6 /6! − · · · + C1 24. (a) = − 1 − x2 /2! + x4 /4! − x6 /6! + · · · + C1 + 1 = − cos x + C 1 − x + x2 − · · · dx = x − x2 /2 + x3 /3 − · · · + C = ln(1 + x) + C (b) (Note: −1 < x < 1, so |1 + x| = 1 + x) 25. (a) Substitute x2 for x in the Maclaurin Series for 1/(1 − x) (Table 11.9.1) and then multiply by x: x =x 1 − x2 ∞ ∞ (x2 )k = k=0 k=0 (c) f (n) (0) = n!cn = (b) f (5) (0) = 5!c5 = 5, f (6) (0) = 6!c6 = 0 ∞ 26. x2 cos 2x = k=0 27. (a) lim x→0 x2k+1 n! if n odd 0 if n even (−1)k 22k 2k+2 (99) x ;f (0) = 0 because c99 = 0. (2k )! sin x = lim 1 − x2 /3! + x4 /5! − · · · = 1 x→0 x x − x3 /3 + x5 /5 − x7 /7 + · · · − x tan−1 x − x = lim = −1/3 x→0 x→0 x3 x3 (b) lim 28. (a) x2 /2! − x4 /4! + x6 /6! − · · · 1 − cos x 1 − 1 − x2 /2! + x4 /4! − x6 /6! + · · · = = 3 /3! + x5 /5! − · · · sin x x−x x − x3 /3! + x5 /5! − · · · = 0 1 − cos x x/2! − x3 /4! + x5 /6! − · · · , x = 0; lim = =0 2 /3! + x4 /5! − · · · x→0 1−x sin x 1 √ 1 11 ln 1 + x − sin 2x = lim ln(1 + x) − sin 2x x→0 x x→0 x 2 (b) lim = lim x→0 = lim x→0 1 1 x2 − sin x2 dx = 29. 0 0 = 11 x2 1 1 4 4 x − x2 + x3 − · · · − 2x − x3 + x5 − · · · 2 3 3 15 3 31 − − x + x2 + · · · 24 2 = −3/2 16 1 1 x + x10 − x14 + · · · dx 3! 5! 7! 17 1 1 13 x− x+ x11 − x15 + · · · 3 7 · 3! 11 · 5! 15 · 7! 1 0 1 1 1 1 + − + ···, =− 3 7 · 3! 11 · 5! 15 · 7! but 1 < 0.5 × 10−3 so 15 · 7! 1 sin(x2 )dx ≈ 0 1 1 1 − + ≈ 0.3103 3 7 · 3! 11 · 5! 401 Chapter 11 1/2 30. 1/2 tan−1 2x2 dx = 0 8 32 128 14 x + · · · dx 2x2 − x6 + x10 − 3 5 7 0 8 32 128 15 23 x − x7 + x11 − x + ··· 3 21 55 105 = 1/2 0 21 81 32 1 128 1 = − + − − ···, 3 7 11 32 21 2 55 2 105 215 but 0.2 1 + x4 31. 1/3 0.2 0 =x+ 1 15 x − x9 + · · · 15 81 1/2 (1 + x2 )−1/4 dx = 0 0 =x− 33. (a) k=0 0 5 15 6 1 x + · · · dx 1 − x2 + x4 − 4 32 128 1/2 0 ∞ xk+1 −C = k+1 ∞ k=0 ∞ k=1 k=1 1 1 (1/2)3 + (1/2)5 ≈ 0.4906 12 32 kxk−1 = xk = x k=1 ∞ kxk k=1 ∞ xk dx − C k=0 xk − C, − ln(1 − 0) = 0 so C = 0. k k=1 (−1) k 0 (1 + x2 )−1/4 dx ≈ 1/2 − (c) Replace x with −x in part (b): ln(1 + x) = − (d) 1/2 1 1 15 (1/2)3 + (1/2)5 − (1/2)7 + · · · , 12 32 896 +∞ +∞ 1 1 (0.2)5 − (0.2)9 + · · · , 15 81 (1 + x4 )1/3 dx ≈ 0.200 1 dx − C = 1−x = = 0.2 + 0 d d x 1 =x =x 2 (1 − x) dx 1 − x dx ∞ 0.2 0.2 15 (1/2)7 < 0.5 × 10−3 so 896 (b) − ln(1 − x) = 2 8 32 − + ≈ 0.0806 3 · 23 21 · 27 55 · 211 1 15 7 13 x + x5 − x + ··· 12 32 896 = 1/2 − but 0 1 (0.2)5 < 0.5 × 10−3 so 15 1/2 32. tan−1 (2x2 )dx ≈ 1 1 1 + x4 − x8 + · · · dx 3 9 dx = 0 but 1/2 128 < 0.5 × 10−4 so 105 · 215 (−1)k k x= k +∞ k=1 (−1)k+1 k x k k+1 converges by the Alternating Series Test. +∞ (e) By parts (c) and (d) and the remark, k=1 (−1)k+1 k x converges to ln(1 + x) for −1 < x ≤ 1. k Exercise Set 11.10 402 34. (a) In Exercise 33(a), set x = 1/3 1 3 ,S= = 2 3 (1 − 1/3) 4 (b) In part (b) set x = 1/4, S = ln(4/3) 35. (a) sinh−1 x = 1 + x2 1 + x2 dx − C = 1 3 5 1 − x2 + x4 − x6 + · · · dx − C 2 8 16 3 57 1 x + · · · − C ; sinh−1 0 = 0 so C = 0. x − x3 + x5 − 6 40 112 = (b) −1/2 (c) In part (e) set x = 1, S = ln 2 −1/2 ∞ =1+ k=1 ∞ (−1/2)(−3/2)(−5/2) · · · (−1/2 − k + 1) 2 k (x ) k! (−...
View Full Document

Ask a homework question - tutors are online